2014
DOI: 10.1007/s10974-014-9386-9
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in sarcoplasmic reticulum calcium content, not myofilament function, contributes to muscle twitch force decline in isolated cardiac trabeculae

Abstract: We set out to determine the factors responsible for twitch force decline in isolated intact rat cardiac trabeculae. The contractile force of trabeculae declined over extended periods of isometric twitch contractions. The force-frequency relationship within the frequency range of 4–8 Hz, at 37 °C, became more positive and the frequency optimum shifted to higher rates with this decline in baseline twitch tensions. The post-rest potentiation (37 °C), a phenomenon highly dependent on calcium handling mechanisms, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
3
15
0
3
Order By: Relevance
“…Unlike in inbred animals, there is very substantial variability between human hearts due to multiple factors such as co-morbid disorders, life-style behaviors, medications, and genetics [35]. Therefore, the phosphorylation status in response to inhibitors needs to be compared within the same hearts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in inbred animals, there is very substantial variability between human hearts due to multiple factors such as co-morbid disorders, life-style behaviors, medications, and genetics [35]. Therefore, the phosphorylation status in response to inhibitors needs to be compared within the same hearts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that this phenomenon is mainly, or even exclusively, due to muscle run-down of the preparation due to alterations in sarcoplasmic-reticulum calcium content [35] while the measured k tr remains stable throughout the course of the several experiments [7, 12, 35]. These previous studies suggest that the run-down that was observed in some of our experiments is not primarily due to the myofilament proteins and has minimal or no effect on our k tr measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Анало-гичные данные сообщают и другие исследователи [9,10]. Отсутствие потенциации инотропного ответа после периодов покоя или отрицательная динамика зависимости инотропной реакции от длительности периодов покоя обусловлены изменением в работе систем, ответственных за поддержание внутрикле-точного гомеостаза ионов кальция [7,10]. Известно, что нарушение Са 2+ -аккумулирующей активности саркоплазматического ретикулума кардиомиоцитов является одним из патогенетических механизмов электрической нестабильности миокарда и угнетения его инотропных возможностей, в том числе и при сер-дечной недостаточности ишемического генеза [13].…”
Section: Discussionunclassified
“…Для этого прекращали электрическую стимуляцию мышц на 4, 6, 8, 10, 12, 16, 20, 30 и 60 сек (период покоя) [7]. Сопоставляли амплитуды регулярного и первого, после периода покоя, циклов сокращение-расслабление (рис.…”
Section: материал и методыunclassified
See 1 more Smart Citation